The Nasal–Brain Drug Delivery Route: Mechanisms and Applications to Central Nervous System Diseases - Yi Qiu; Shiyuan Huang; Li Peng; Li Yang; Guosong Zhang; Tao Liu; Fang Yan; Xi Peng (MedComm)
ABSTRACT The blood–brain barrier (BBB) is a highly selective and protective barrier that restricts the entry of most therapeutic agents into the central nervous system (CNS), posing a significant challenge for the treatment of CNS diseases. The nose‐to‐brain drug delivery (NBDD) route has emerged as a promising strategy to bypass the BBB, offering direct, noninvasive, and efficient transport of drugs to the brain. This review begins with a concise overview of the BBB structure and its biofunctions, followed by an in‐depth discussion of the mechanisms underlying the nose‐to‐brain pathway, including the olfactory and trigeminal nerve routes, and respiratory pathway. We further highlight the therapeutic research development of neurodegenerative diseases, acute neurological diseases, brain tumor, and psychiatric disorders when using NBDD drugs encompassing small‐molecule drugs, proteins, peptides, nucleic acids, siRNA, and herbal compounds, in which we also introduce innovative delivery systems, including nanocarriers and novel platforms such as exosomes, which enhance drug stability, targeting efficiency, and bioavailability. In addition, we provide a comprehensive overview of recent clinical advancements in therapeutics delivered via the intranasal route for CNS diseases. Finally, we discuss the challenges and future directions of NBDD, emphasizing its potential to transform the treatment landscape for CNS disorders.